2021
DOI: 10.1051/swsc/2020073
|View full text |Cite
|
Sign up to set email alerts
|

Inferring depth-dependent plasma motions from surface observations using the DeepVel neural network

Abstract: Coverage of plasma motions is limited to the line-of-sight component at the Sun's surface. Multiple tracking and inversion methods were developed to infer the transverse motions from observational data. Recently, the DeepVel neural network was trained with computations performed by numerical simulations of the solar photosphere to recover the missing transverse component at surface and at two additional optical depths simultaneously from the surface white light intensity in the Quiet Sun. We argue that deep le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…In our work, we pick σ = 10, as it produces the strongest correlation. Following the analyses in Schrijver et al (2006) and Tremblay et al (2021), we consider three other correlation metrics between the reference STAGGER velocities and the velocities obtained from inversions: the spatially averaged relative error…”
Section: Transverse Velocity Inversion Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our work, we pick σ = 10, as it produces the strongest correlation. Following the analyses in Schrijver et al (2006) and Tremblay et al (2021), we consider three other correlation metrics between the reference STAGGER velocities and the velocities obtained from inversions: the spatially averaged relative error…”
Section: Transverse Velocity Inversion Methodsmentioning
confidence: 99%
“…) inTremblay et al (2021). For FLCT, the values of these metrics are (E rel = 1.09, C = 0.35, A = 0.21).…”
mentioning
confidence: 99%
“…DeepVel can estimate the horizontal velocity at various heights in the solar atmosphere without averaging. Tremblay et al (2021a) showed that the Pearson linear correlation between the estimation and the answer was approximately 0.8. The correlation increases when the horizon- tal velocity fields are averaged over several granular lifetimes (Tremblay et al 2018); the increment of the accuracy by taking the average shows the same trend as the LCT.…”
Section: Introductionmentioning
confidence: 98%